Engineered G-protein coupled receptors are powerful tools to investigate biological processes and behaviors - Nichols, Charles D.; Roth, Bryan (Frontiers in Molecular Neuroscience, 2009)
Understanding how discreet tissues and neuronal circuits function in relation to the whole organism to regulate physiological processes and behaviors is a fundamental goal of modern biological science. Powerful and important new tools in this discovery process are modified G-protein coupled receptors (GPCRs) known as ‘Receptors Activated Solely by Synthetic Ligands (RASSLs),’ and ‘Designer Receptors Exclusively Activated by a Designer Drug (DREADDs).’ Collectively, these are GPCRs modified either through rational design or directed molecular evolution, that do not respond to native ligand, but functionally respond only to synthetic ligands. Importantly, the utility of these receptors is not limited to examination of the role of GPCR-coupled effector signal transduction pathways. Due to the near ubiquitous expression of GPCRs throughout an organism, this technology, combined with whole animal transgenics to selectively target expression, has the ability to regulate activity of discreet tissues and neuronal circuits through effector pathway modulation to study function and behavior throughout the organism. Advantages over other systems currently used to modify in vivo function include the ability to rapidly, selectively and reversibly manipulate defined signal transduction pathways both in short term and long term studies, and no need for specialized equipment due to convenient systemic treatment with activating ligand.